The Effect of Dhikir Therapy to Reduce Anxiety in Pregnant Women in Fatiya Clinic, Sleman Regency - Reza Mina Pahlewi (Syntax Literate, 2023)
Physical and psychological changes in pregnant women cause anxiety that can affect fetal development. Dhikr therapy is an effort to reduce the anxiety of pregnant women by remembering the existence of Allah in the form of pronunciation with the tongue or heart. Therefore, the purpose of this study was to examine the effect of dhikr therapy in reducing anxiety in pregnant women. The participants consisted of 14 pregnant women with gestational ages between 4 to 34 weeks, ages between 20 to 40 years, and were classified into two groups, namely the experimental group and the control group, where the experimental group received dhikr therapy while the control group did not receive therapy (waiting list). The design of this study used a quasi-experimental design with pretest-posttest and follow-up. anxiety scale for pregnant women Anxiety Scale for Pregnancy (API)Data from both groups were analyzed by independent sample t-test, then the value of t = -4.708 and p = 0.001 (p < 0.01) is known. This shows that there is a difference in the level of anxiety of pregnant women between the experimental group and the control group, where the experimental group experienced a significant decrease in the anxiety of pregnant women compared to the control group. Based on the results of this study, it was concluded that dhikr therapy had an effect on reducing the anxiety level of pregnant women.